Gone fishing, other side of the world - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In July 2002, the first fisheries agreement was signed between the EU and the Pacific island nation of Kiribati. For the next 3 years, European vessels, mainly from France, Portugal and Spain, can fish for tuna beyond the 12-mile coastal band. Each...